Trends and frontiers in coal mine groundwater research: insights from bibliometric analysis - Yang Xiang; Suping Peng; Wenfeng Du (Geomechanics and Geophysics for Geo-Energy and Geo-Resources, 2023)
Abstract Globally, studying the impact of coal mining on groundwater remains challenging. This is because the exploitation of coal resources and the sustainable development of groundwater resources involve economic, social, and environmental aspects. Over the last few decades, the number of publications on groundwater-related studies in coal mining areas has increased. However, they are not currently reviewed in a widely visible manner through bibliometric analyses. This study investigated groundwater research in coal mining areas worldwide using scientometric analysis based on 1196 articles from the Web of Science database to provide a global perspective and gain quantitative insight into research frontiers and trends in the field by mapping existing knowledge. We analyzed the key contributors and development processes of coal mine groundwater research and identified four research frontiers based on scientometric mapping results with an understanding of the research field: numerical modeling, conceptual modeling and mechanisms, feedback mechanisms between anthropogenic-environmental systems and groundwater systems, ground subsidence management, groundwater quality evaluation and risk assessment, and groundwater resource management in coal mines. Finally, we summarize the current challenges and propose methods to promote the green mining of coal resources and the sustainable development and management of groundwater resources.